Effect of Organic Amendments on Life Cycle Development of Pasteuria penetrans (bacterial parasite) on Root-Knot Nematode (Meloidogyne javanica) infecting Tomato (Indian Journal of Nematology, 2024)
Root-knot nematodes, Meloidogyne spp. are one of the most important pests of tomato crop. Among the promising biocontrolagents of plant parasitic nematodes, the bacterial parasite- Pasteuria penetrans has been investigated in detail and found to hold potential for the management of Meloidogyne spp. An experiment was carried out underscreen house conditions of Departmentof Nematology of CCS Haryana Agricultural University, Hisar, to study the effect of organic amendments (neem cake, mustard cake,castor cake and farmyard mannure) on the life cycle development of P. penetrans on M. javanica infecting tomato. All life cycle stagesof bacterium viz.,microcolony, thallus, quartets, diads, immature spore and mature spore were observed and nematode viz., parasiticJ2, spike tail stage, immature and mature female were observed and compared for all the organic amendments. The result revealedthat the life cycle of P. penetrans on root-knot nematode was completed in all the organic amendments but, the life cycle was wellsynchronised with root-knot nematode when it was integrated with mustard cake.There was slight delay in life cycle of bacteriumwhere castor cake, neem cake and FYM were applied. However, both nematode and bacteriumcompleted their life cycle in all theorganic amendments.